Empowering Students: Innovative Management of Extracurricular Activities for Greater Achievement - Tawakkal, Muhammad; Nawas, M. Zuhri Abu; Sanusi, Syamsu (International Journal of Asian Education, 2025)
Extracurricular activities are a vital component in the educational process that supports holistic student development, encompassing intellectual, emotional, and social growth. This study aims to analyze the management of extracurricular activities at SMA Negeri 10 Luwu Utara and its impact on student motivation and achievement. Using a qualitative research design, data collection was conducted through observations, interviews, and documentation involving extracurricular supervisors, school officials, and students. The findings reveal that the management process follows four main stages: planning, organizing, implementing, and evaluating. The structured management approach significantly enhances student skills, fosters leadership, and boosts student engagement. However, several challenges were identified, including overlapping schedules, limited funding, and time constraints, which hinder the optimal execution of extracurricular programs. The study emphasizes that innovative management strategies, supported by the active role of teachers, school officials, and parents, are essential to maximize the benefits of extracurricular activities. Furthermore, the research highlights that effective extracurricular management not only improves student motivation but also enhances academic performance and character development. By addressing the existing challenges and strengthening collaboration among stakeholders, extracurricular activities can serve as a powerful tool to support student achievement and personal growth. This study provides valuable insights for educational institutions in developing more effective strategies to manage extracurricular programs and create a supportive learning environment that nurtures student potential in both academic and non-academic aspects.